2016
DOI: 10.7150/jca.15274
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Activation in Cervical Cancer Cells Induces Cell Growth Arrest with the Involvement of the Nuclear Receptor NR4A2

Abstract: Cervical cancer is a second leading cancer death in women world-wide, with most cases in less developed countries. Notch signaling is highly conserved with its involvement in many cancers. In the present study, we established stable cervical cell lines with Notch activation and inactivation and found that Notch activation played a suppressive role in cervical cancer cells. Meanwhile, the transient overexpression of the active intracellular domain of all four Notch receptors (ICN1, 2, 3, and 4) also induced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…Our previous study also showed that NR4A2 stimulated cervical cancer cell growth [11]. Presently, we found that NR4A2 was up-regulated in many primary HCC tissues and immortal HCC cell lines, and co-existed with Notch1.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Our previous study also showed that NR4A2 stimulated cervical cancer cell growth [11]. Presently, we found that NR4A2 was up-regulated in many primary HCC tissues and immortal HCC cell lines, and co-existed with Notch1.…”
Section: Discussionmentioning
confidence: 52%
“…We also observed the effects of Notch1 on certain genes in cervical cancer Hela cells [11]. NR4A2, as well as VPA, modulated the expression of these genes in HCC HTB-52 cells [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathways are composed of various cytokines and transcription factors and among these pathways, the Notch-Hes signaling transduction pathway is the most important pathway. If there is abnormity of Notch signaling pathway, the cells cannot differentiate normally, thus there is possibility of oncogenesis, and it has been reported that the Notch receptor is abnormally expressed in numerous human solid tumor types including cervical, head and neck, endometrial, kidney, lung and breast cancer, pleural mesothelioma and salivary gland tumors) and hematological malignancies (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of Nurr1 was shown to reduce anchorage-independent growth by increasing anoikis, as demonstrated by the increase in DNA fragmentation. Apart from inhibiting apoptosis, Sun et al reported that Nurr1 increases cell proliferation [ 25 ]. Notch activation (by overexpression of four Notch receptors: ICN1, 2, 3, 4) suppresses tumor growth in cervical cancer with ICN1 displaying the most significant antitumor effect.…”
Section: Expression and Function Of Nurr1 In Cancermentioning
confidence: 99%